New perspectives in benthic deep-sea microbial ecology - Corinaldesi, Cinzia (Frontiers in Marine Science, 2015)
Deep-sea ecosystems represent the largest and most remote biome of the biosphere. They play a fundamental role in global biogeochemical cycles and their functions allow existence of life on our planet. In the last 20 years enormous progress has been made in the investigation of deep-sea microbes, but the knowledge of the microbial ecology of the soft bottoms (representing >90% of the deep-sea floor surface) is still very limited. Deep-sea sediments host the largest fractions of Bacteria, Archaea and viruses on Earth, and potentially, a high diversity. At the same time, available results from metagenomics suggest that a large fraction of microbial taxa is completely unknown to science. Estimating the diversity of deep-sea benthic microbes and understanding their functions are some of the challenges of absolute priority, not only for deep-sea microbial ecology, but also for the entire research field of life sciences. The achievement of these goals, given the importance of the deep-sea microbial life for the functioning of the global biosphere, will open new perspectives for the comprehension of adaptation processes to the impact of global changes.